Establishment and application of a dynamic tumor-vessel microsystem for studying different stages of tumor metastasis and evaluating anti-tumor drugs. Issue 30 (31st May 2019) - Jing, Bolin; Luo, Yong; Lin, Bingcheng; Li, Jianjun; Wang, Zhuo A.; Du, Yuguang
Abstract : The different stages of the cancer metastasis were reproduced individually on a novel tumor-vessel co-culture microsystem. Abstract : Tumor metastasis is one of the main causes of cancer-related death, and it is difficult to study the whole process of tumor metastasis in vivo due to the complex physiological environment in the body. Therefore, it's crucial to develop simple and physiologically relevant in vitro cancer models to study the metastasis process, especially different phases of tumor metastasis. A novel microfluidic tumor-vessel co-culture system was established to reproduce the different phases of cancer metastasis (proliferation, migration, intravasation and adherence) individually in vitro for the first time. It was observed that blood vessels with fluid flow had big impact on metastasis of liver cancer cells HepG2 and breast ones MDA-MB-231. In particular, it was found that both HepG2 and MDA-MB-231 cells migrated in the direction of "blood flow". Furthermore, MDA-MB-231 cells invaded through paracellular mode disrupting the intercellular endothelial junctions, whereas HepG2 cells engaged in transcellular intravasation through transcellular process. Compared with traditional assays, much more potent inhibition of 5-fluorouracil (5-Fu) on different phases of tumor metastasis was observed on the microsystem. In summary, the microfluidic device yielded abundant information about each phase of tumor metastasis, and would provide a powerful platform for use in drug screening, toxicology studies, and personalized medicine in future.